Factors affecting willingness to pay for green products among undergraduate students in UTAR - Lai, Zheng Hao; Ong, Jia Yi; Tan, Suk Li; Tio, Yu Xuen (2020)
Even though green products play an important role in reducing the environmental problems, the consumers’ low willingness to pay for green products has caused the global demand for green products to be lower than expected. Therefore, many studies concerning the willingness to pay for green products have been conducted among undergraduate students around the world especially in developed countries. However, the role of undergraduate students, studying in private universities in developing countries like Malaysia, has often been overlooked although they are the main future consumers for the green products in these countries. Hence, on the basis of the Extended Theory of Planned Behaviour, this study seeks to determine the influences of attitude towards green products, subjective norm, perceived behavioural control, environmental concern and environmental knowledge on the willingness to pay for green products among undergraduate students in UTAR. In order to collect the data in this study, questionnaires were distributed to 371 UTAR Kampar undergraduate students, which were selected by employing the quota sampling technique. Then, Multiple Linear Regression Analysis was conducted by using the Statistical Package for the Social Sciences (SPSS) version 26.0. The results of the analysis indicate that the attitude towards green products, subjective norm, perceived behavioural control, environmental concern and environmental knowledge have significant influences on the willingness to pay for green products. Therefore, it is recommended that universities, government agencies and religious organizations should focus on these key factors when they attempt to improve the willingness to pay for green products.